IMPACT OF ESG REGULATIONS ON SUSTAINABLE BUSINESS PRACTICES: EVIDENCE FROM INDONESIA - Hakim, Muhammad Taufiqul; Fuad, Fuad (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2024)
This research project examines the correlation between ESG (Environmental, Social, and Governance) regulations and sustainable business practices among small and medium-sized enterprises (SMEs) in Indonesia. Through qualitative interviews and a review of relevant literature, this study seeks to identify the obstacles and advantages that Indonesian SME's encounter when attempting to incorporate ESG principles into their operations. Proactively promoting ESG-related policies to address environmental, social, and governance challenges has been the Indonesian government. However, little is known about the efficacy and implications of these regulations, specifically for SMEs with limited resources. By assessing the influence of ESG regulations on the behaviour of small and medium-sized enterprises (SMEs), this study aims to address this knowledge deficit by identifying barriers to adherence and viable approaches to promote sustainable entrepreneurship